Evaluasi Kepuasan E-commerce Supply Chain Management dari Sisi Kepercayaan dan Kualitas Layanan Konsumen - Eka Sudarusman; Sri Lani; RR. Rani Kusumo Wardhani (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
Supply Chain Management (SCM), involves various parties, either directly or indirectly, to fulfill customer demands. Manufacturers and suppliers are part of the supply chain, including shipping, warehousing, retailers, as well as the customers themselves. In any organization, the supply chain consists of all the functions involved in receiving and fulfilling customer demands. The main concern of SCM is to provide customers with the right product, at the right cost, at the right time, with the right quality and in the right quantity. This study aims to evaluate the satisfaction of SCM e-commerce in terms of trust and customer service quality. The results show that trust and service quality have a significant positive effect on e-commerce SCM. Service quality partially mediates trust in customer satisfaction.